Mimusops elengi Flower Hydroethanolic Extract as A Safe Antioxidant Ingredient for Cosmeceutical Applications - Keawbankrud, Wannisa; Techaoei, Surachai; Thungmungmee, Suradwadee; Jamkom, Khemjira; Chamutpong, Siriphatr; Rachawat, Patamaporn; Sricharoen, Phitchan; Pheedee, Nattharika; Phetkeereerat, Saowanee; Seekhaw, Siriwimon; Pittayanon, Rawisara; Nakyai, Wongnapa (Trends in Sciences, 2025)
Natural phenolic antioxidants have gained increasing attention for their safety and effectiveness in cosmeceutical products. Among these, the flowers of Mimusops elengi (M. elengi), traditionally used in Thai medicine, are known for their rich content of phenolic and terpene compounds, which contribute to their therapeutic potential. This study investigates the antioxidant activity and skin safety of M. elengi flower hydroethanolic extract (MEFE) for cosmeceutical applications. The MEFE was prepared through maceration, and the total phenolic content was measured using the Folin-Ciocalteu method. FT-IR and UV-VIS absorption spectroscopy were employed to confirm the presence of phenolic functional groups. Antioxidant activities were tested using DPPH, FRAP, ABTS, and NO assays to assess the MEFE’s radical scavenging efficiency. In addition, cytotoxicity assays on human skin cells, including keratinocytes (HaCaT), fibroblasts, and melanocytes (B16F1), were conducted to ensure safety. A body serum lotion containing the 2.00 % w/w MEFE was formulated and evaluated for stability. Results showed that the extract contained phenolics 77.02 ± 0.01 mg GAE/g and exhibited strong antioxidant activities with IC50 values of 33.16 ± 1.04, 4.16 ± 1.06, 132.84 ± 1.05, and 293.10 ± 1.03 µg/mL for DPPH, FRAP, ABTS, and NO assays, respectively. Cytotoxicity testing confirmed low toxicity, with IC50 values of 483.28 ± 31.56 µg/mL for keratinocytes, >1,000.00 µg/mL for fibroblasts, and 630.51 ± 17.59 µg/mL for melanocytes. The 2.00 % MEFE body serum lotion demonstrated good physical stability, suggesting that the MEFE is a promising ingredient for skincare products. Therefore, further studies are needed to identify the phytoconstituents in the MEFE, and explore the molecular mechanisms by which the MEFE inhibits skin aging from oxidative stress. Additionally, clinical trials are needed to evaluate its overall safety through a skin irritation test and to assess its efficacy in the 2.00 % MEFE body serum lotion. HIGHLIGHTS The ethanolic extract of Mimusops elengi flowers (MEFE) serves as a potent natural source of phenolic antioxidants, evaluated through DPPH, ABTS, FRAP, and NO scavenging assays. The effective antioxidant dose of the MEFE does not exhibit toxicity to skin cells, indicating its safety for cosmeceutical applications. The body serum lotion formulated with the 2.00 % w/w MEFE was developed, exhibiting good stability in physicochemical properties. GRAPHICAL ABSTRACT